2010
DOI: 10.1021/ol102194c
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Oxidative Coupling Reactions with Aryltrimethylsilanes

Abstract: During continuing studies with a novel oxidative gold oxyarylation reaction, arylsilanes were found to be competent coupling partners, providing further evidence for an intramolecular electrophilic aromatic substitution mechanism. While providing complementary yields to the previously described boronic acid methods, the use of trimethylsilanes reduces the observation of homocoupling byproducts and allows for facile intramolecular coupling reactions.With the development of transition metal-catalyzed cross-coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(76 citation statements)
references
References 42 publications
2
72
0
2
Order By: Relevance
“…Independent reports by Toste and Russell demonstrated that aryltrimethylsilanes are similarly effective in the majority of cases using both intra-and intermolecular nucleophiles. [46] As for arylboronic acids, the presence of fluoride derived from the external oxidant, Selectfluor, is thought to aid the nucleophilicity of the aryl group through the formation of a strong Si À F bond. Arylsilanes are desirable sources of aryl moieties for oxidative coupling reactions, since they are readily prepared and purified and are comparatively stable with respect oxidation by the external oxidant.…”
Section: Cascade Nucleophilic Addition-oxidative Coupling Reactionsmentioning
confidence: 99%
“…Independent reports by Toste and Russell demonstrated that aryltrimethylsilanes are similarly effective in the majority of cases using both intra-and intermolecular nucleophiles. [46] As for arylboronic acids, the presence of fluoride derived from the external oxidant, Selectfluor, is thought to aid the nucleophilicity of the aryl group through the formation of a strong Si À F bond. Arylsilanes are desirable sources of aryl moieties for oxidative coupling reactions, since they are readily prepared and purified and are comparatively stable with respect oxidation by the external oxidant.…”
Section: Cascade Nucleophilic Addition-oxidative Coupling Reactionsmentioning
confidence: 99%
“…Intramolecular coupling of an olefin and a tethered arylsilane occurred in a 6-endo-trig fashion to give tetrahydronaphthalene 14 in a yield similar to that obtained with Selectfluor as the oxidant [10] (Scheme 2, top). By contrast, the two-component heteroarylation of olefins bearing tethered O-or N-nucleophiles did not proceed to afford the expected tetrahydrofurans or pyrrolidines: in the case of 4-penten-1-ol, a complex mixture of products was obtained, whilst N-(4-pentenyl)tosylamide furnished a 9:1 mixture of piperidine 15 and pyrrolidine 16 (Scheme 2, bottom).…”
Section: Scope-monosubstituted Olefinsmentioning
confidence: 73%
“…[10] In addition, the combination of nucleophilic promoters (e.g., TBAF, TBAT = tetrabutylammonium triphenyldifluorosilicate) and alternative oxidants (e.g., PhIA C H T U N G T R E N N U N G (OAc) 2 ) afforded only traces of the desired oxyarylation products. [9] The evident inhibitory effect of basic additives on the transformation prompted us to assay the oxyarylation of 1-octene under Brønsted acidic conditions (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations